Diversity of Convolvulaceae from Meruoca Massif, Ceará, Brazil - Santos,Diego (2021)
Abstract We present the taxonomic treatment of Convolvulaceae for the Meruoca Massif, located in the Northwest region of the Ceará state, where there are remnants of Tropical Pluvial Sub-deciduous Forest (Dry Forest) and Tropical Pluvial-Nebular Rainforest (Wet Forest). The present study was based on the morphological analysis of specimens collected in the field and from the collections EAC, HUEFS, HUVA, PEUFR, and SPF. We recorded 24 species distributed in four genera: Ipomoea (18 species), Jacquemontia (three species), Distimake (two species), and Camonea (one species). We report the first records of I. cearensis for Atlantic Forest and I. aristolochiifolia to the state of Ceará. The taxonomic treatment includes identification key, morphological descriptions, geographic distribution, taxonomic and ecological comments, the period of flowering and fruiting, and photos and illustrations of the diagnostic characters.